2015
DOI: 10.1093/jxb/erv227
|View full text |Cite
|
Sign up to set email alerts
|

From lateral root density to nodule number, the strigolactone analogue GR24 shapes the root architecture of Medicago truncatula

Abstract: Running title: Strigolactones and root architecture in M. truncatula Date of submission: Number of figures: 6 Number of black and white figures: 5 Number of colour figures: 1 Number of tables: 0 Total word count: 7592 3 For the first time, strigolactones are shown to influence lateral root development and nodulation in Medicago truncatula. Nodulation is affected at early stages and crosstalks with ethylene signalling are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Moreover, they showed that GR24 increased the nodule number in wild-type plants (Foo and Davies 2011). More recently, in Medicago truncatula it was shown that the effect of GR24 on nodule number is dose-dependent (De Cuyper et al 2015). De Cuyper and co-workers showed that low concentrations (0.1 μM) of GR24 had a positive effect, while higher concentrations negatively affected the number of nodules.…”
Section: Plant-microbe Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they showed that GR24 increased the nodule number in wild-type plants (Foo and Davies 2011). More recently, in Medicago truncatula it was shown that the effect of GR24 on nodule number is dose-dependent (De Cuyper et al 2015). De Cuyper and co-workers showed that low concentrations (0.1 μM) of GR24 had a positive effect, while higher concentrations negatively affected the number of nodules.…”
Section: Plant-microbe Interactionsmentioning
confidence: 99%
“…One of the functions of SLs below-ground is to regulate root development in response to phosphorus shortage (De Cuyper et al 2015;Kapulnik et al 2011a;Koltai 2011;Ruyter-Spira et al 2011). Interestingly, SL biosynthesis is promoted by P-limiting conditions (Table 1) (Foo et al 2013b;López-Ráez et al 2008a;Yoneyama et al 2007Yoneyama et al , 2012, and it has been suggested that they play a pivotal role as modulators of the coordinated development of roots and shoots under these unfavourable conditions.…”
Section: Sls and Root System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Strigolactones (SLs) are recently defined plant hormones with roles in mycorrhizal symbiosis and shoot and root architecture (Waters et al ). Application of low concentrations of GR24, a synthetic SLs analogue, to M. truncatula and pea could slightly induce nodule number (Soto et al ; Foo and Davies ; De Cuyper et al ), indicating that SLs exert a positive role in nodule formation in several legume species. However, high concentrations of GR24 strongly inhibited nodulation (De Cuyper et al ), suggesting that promotion of SLs in nodulation depends on an optimal range of SLs.…”
Section: Strigolactonesmentioning
confidence: 99%
“…Application of low concentrations of GR24, a synthetic SLs analogue, to M. truncatula and pea could slightly induce nodule number (Soto et al ; Foo and Davies ; De Cuyper et al ), indicating that SLs exert a positive role in nodule formation in several legume species. However, high concentrations of GR24 strongly inhibited nodulation (De Cuyper et al ), suggesting that promotion of SLs in nodulation depends on an optimal range of SLs. SLs biosynthesis genes can also be induced by S. meliloti or NFs (Breakspear et al ).…”
Section: Strigolactonesmentioning
confidence: 99%